2019
DOI: 10.1111/ger.12398
|View full text |Cite
|
Sign up to set email alerts
|

Patients' self‐reported measures of oral health—A validation study on basis of oral health questions used in a large multi‐country survey for populations aged 50+

Abstract: Objective To assess the validity of patient self‐reported oral health measures as used in a large multi‐country survey for populations aged 50+. Background Information on people's oral health status is important for assessing oral health needs within populations. However, clinical examination is not always possible. Patient self‐reported measures may provide an alternative when time and other resources are scarce. Materials and methods Using oral health items from the Survey of Health, Ageing and Retirement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Thus, our estimation might be biased if the utilization of fluoride resources differs by regions; however, the frequency of tooth brushing was not different by region in Adult Dental Health Survey 2009 38 . Moreover, data on the number of teeth and IADL was self‐reported; however, high accuracy of self‐reports for number of teeth has been reported previously 54 …”
Section: Discussionmentioning
confidence: 98%
“…Thus, our estimation might be biased if the utilization of fluoride resources differs by regions; however, the frequency of tooth brushing was not different by region in Adult Dental Health Survey 2009 38 . Moreover, data on the number of teeth and IADL was self‐reported; however, high accuracy of self‐reports for number of teeth has been reported previously 54 …”
Section: Discussionmentioning
confidence: 98%
“…spearman's ρ >0.20), but adjusting for these variables did not change our findings. A further limitation is related to the self-reported outcome; however, the measurement has been well validated in clinical care settings (Kroenke et al ., 2001; Sekundo et al ., 2019). Finally, the findings may not be directly transferrable to other countries or settings, although the prevalence of severe tooth loss in the USA is similar to the global population (Kassebaum et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate whether the effect of tooth loss varies by population characteristics, analyses stratified by age, year of birth, gender, median household income and dental care utilisation were performed. We also performed a sensitivity analysis by assigning mean, median and mode of the clinically examined number of lost teeth reported in a previous study (Sekundo et al ., 2019) for the brackets of self-reported 1–5 or 6–27 lost teeth.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that it is important to use clinical data along with SROH measures [ 12 ]. Although oral examinations are considered the gold standard to assess oral health status [ 13 ], SROH is a valid method for epidemiological data collection [ 14 , 15 ]. Perceptions of oral health vary among ethnic groups and people of different cultural backgrounds [ 5 ].…”
Section: Introductionmentioning
confidence: 99%